Avaliação da população canina da zona urbana do Município de Araçatuba, São Paulo, SP, Brasil - Nunes, Caris Maroni [UNESP]; Martines, Dejanira de A.; Fikaris, Stélios; Queiroz, Luzia Helena [UNESP] (My University, 1997)
Planning control programs, for diseases such as rabies requires information on the size and structure of the dog and cat population. In order to evaluate the dog population of the urban area of Araçatuba city, S. Paulo State, Brazil, a survey was conducted using a questionnaire to interview members of households. Eighty-eight districts were visited (37,778 houses) and the interview was possible at 77.93% of these. Human population size evaluated was 113,157 inhabitants. Houses that owned animals represented 55.2%, 26,926 of the animals concerned were dogs and 5,755 were cats. Of the dogs, 56.64% were 1-4 year olds and males represented 56.2% of the total population. Dog: person ratio was estimated at 2.8 dogs to every 10 persons, almost 3 times the ratio hitherto estimated and used in the planning of rabies vaccination campaigns.
Evaluation of dog population in an urban area of Southeastern Brazil
Keywords: Dogs; Rabies, prevention and control; Urban population, statistics; rabies vaccine; animal; Brazil; dog; dog disease; human; immunology; organization and management; population density; preventive health service; rabies; statistics; urban population; Animals; Dog Diseases; Humans; Immunization Programs; Population Density; Rabies; Rabies Vaccines; Urban Population